1992
DOI: 10.2334/josnusd1959.34.224
|View full text |Cite
|
Sign up to set email alerts
|

Use of Two Miniplates for Intermaxillary Skeletal Fixation in the Treatment of Jaw Deformity and Fracture.

Abstract: Special techniques of skeletal intermaxillary fixation are described, which may be used in edentulous patients or those with many missing teeth or multiple fractures of the jaw. Two such cases are described in which the usual fixation techniques could not provide sufficient stabilization because of linguoversion and mesioversion or lack of teeth, resulting in inability to maintain a vertical interocclusal relationship.Two long eight-hole Champy miniplates were therefore used distally to the canines on both sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…14 A search for articles on this subject in the English language between 1980 and 2010 in the PubMed databank produced only 3 similar cases. 15, 16 Wolfe et al 15 reported a case in which only 1 miniplate in the anterior region was used to provide intermaxillary fixation in an edentulous patient with multiple facial fractures following an assault with a baseball bat. This intermaxillary fixation remained for 8 weeks, and no complications were observed in this timeframe.…”
Section: Discussionmentioning
confidence: 99%
“…14 A search for articles on this subject in the English language between 1980 and 2010 in the PubMed databank produced only 3 similar cases. 15, 16 Wolfe et al 15 reported a case in which only 1 miniplate in the anterior region was used to provide intermaxillary fixation in an edentulous patient with multiple facial fractures following an assault with a baseball bat. This intermaxillary fixation remained for 8 weeks, and no complications were observed in this timeframe.…”
Section: Discussionmentioning
confidence: 99%
“…B. mittels Klemmen) in Kontakt gebracht, bevor die Frakturzone ruhig gestellt wird. Ein einfaches und interessantes Verfahren zur Fragmentimmobilisation durch maxillomandibuläre Fixation im zahnlosen Kiefer ist die Applikation von Miniplatten zur Distanzüberbrückung zwischen Ober-und Unterkiefer unter Aufrechterhaltung der vertikalen Kieferrelation [19,20]. Dazu werden die Plattenenden von ca.…”
Section: Therapeutische Optionenunclassified